The determination of plasma adrenocorticotropic hormone during the treatment of women experiencing dog phobia - Odendaal, Johannes Stefanus Joubert (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Ethology))--University of Pretoria, 1999.